Wings of fire. The graphic novel. Book one, Dragonet prophecy - Deutsch, Barry; Holmes, Mike; Sutherland, Tui, 1978- (New York : Graphix, 2018)
Clay and the other four MudWing dragonets were stolen from their homes while they were still in their eggs and hidden for years in order to fulfill a prophecy claiming that the dragonets would end the war between the dragon tribes, but not all of the dragonets want their destiny.
Based on: The dragonet prophecy / by Tui T. Sutherland.
Kirkus Starred, December 2017
3.4
3-6
GN280L
Keywords: Dragons -- Juvenile fiction; Prophecies -- Juvenile fiction; Dragons -- Comic books, strips, etc. -- Fiction; Prophecies -- Comic books, strips, etc. -- Fiction; Fantasy comics; Graphic novels; Graphic novels; Graphic novel adaptations; Comics (Graphic works)